Knowledge, Attitudes and Practices of Mothers for Prevention of Burn Among Children Under 5 Years at Home in Baghdad Al-Rusafa 2016: Pengetahuan, Sikap dan Praktik Ibu dalam Pencegahan Luka Bakar pada Anak di Bawah 5 Tahun di Rumah di Baghdad Al-Rusafa 2016 - Jabbar, Najwa Adnan Abdul (Indonesian Journal on Health Science and Medicine, 2024)
Objectives -To assess the mother's knowledge, attitudes about burns, and practices of first aid management among children under 5 at home. Methods: -A descriptive cross-sectional study was conducted during the period from 1st of January to 31 of May 2016.A convenient sample was used in this study. The total number was 300 mothers attending primary health care centers (AL- -Mustansiriya Family Medicine Center, AL- Sulaikh Family Medicine Center,Ure Family Medicine Medical Center and Al-Baldiat primary health care centers), in Baghdad/AL-Rusafa. Data was collected through introducing a questionnaire to the mothers containing data about sociodemographic characteristics and mothers, attitude, and practices(KAP) towards risk factors of bum and the practice of first aids Results: -Total number of mothers (300) attending PHC in Baghdad/Rusafa aged from l 7-45 years. With regards to knowledge about bum the results revealed that between 47-59% of the participants completely agreed with the right statement or disagreed with the incorrect one and there was a smaller percentage partially agreed or disagreed with the statements related to knowledge about burn, about 6- 17% of the participants reported no idea about the correct answer. More than three quarters (70.3-94.7 0/0) of the participants reported correct attitude about possible risk factors and prevention of bum accidents, and a nearly similar percentage of participants (75.3-91.3%) reported connect practices about first aid related to burn isianagcnient at home. A significant association was reported between a score of KA1° and each of the educational level and history of attendees trailing coin scs ( =0.001, 0.04) respectively. Highlights: Assess mothers' knowledge, attitudes, and practices on burn management. Cross-sectional study of 300 mothers in Baghdad primary health centers. Most participants showed correct attitudes, practices; knowledge linked to education, training. Keywords: Burn, childreli, knowledge, Attitudes, Practice, mothers